ADMA, neutrophil to lymphocyte, platelet to lymphocyte ratios and phase angle: effects on inflammation and nutrition in hemodialysis patients - Gürlek Demirci, Bahar; Karakan, Mine Şebnem (The European Research Journal, 2024)
Objectives: Neutrophil/lymphocyte ration (NLR) and platelet/lymphocyte ratio (PLR) levels can be used as systemic infallamotory parameters. Asymmetric dimethyl arginine (ADMA) inhibits endothelial nitric oxide synthase. Phase Angle (PhA) is a potential paremeter to screen for inflammatory abnormalities. In present study we aimed to determine the relations between NLR, PLR, ADMA, and PhA in terms of early markers for nutritonal status in addition to their well-known role in inflammation. Methods: A total of 89 patients undergoing maintenance hemodialysis 3 days a week at least 6 months were enrolled. To assess nutritional status, we performed the dietary questionnaire and mini nutritional assessment score (MNAS). ADMA was measured by ELISA. NLR and PLR are calculated from monthly complete blood count tests. Patients were divided into 2 groups accordng to NLR levels as group 1 (NLR≥4.6; n=48) ve and group 2 (NLR